Le President Mobutu et le Premier Ministre Sous L’acte Constitutionnel de la Transition: Duel ou Duo? - Kangashe, Jean-Louis Esambo (Afrika Focus, 1998)
Since the beginning of the democratic process in Mobutu's Zaire, in April 1990, a judicial and political debate has continued to divide the opinion on the power sharing within the executive. The Transitional Constitutional Act, a result of the political negotiations of the Palais du Peuple, was aimed at resolving the competence conflicts between the President of the Republic and the Prime Minister. This constitutional framework, however, was unable to avoid neither the possibility of a "duel" nor the avatars of an alleged "duo" between the two main representatives of the executive function. In the meantime, the frequent violations of the constitution by the head of state have shown that power sharing within a parliamentary system could not come to a compromise with the power practice under Mobutu. KEY WORDS: President, politics, Prime Minister, constitution, Zaire